Wide localized solitons in systems with time- and space-modulated nonlinearities - Arroyo Meza, L. E. [UNESP]; Dutra, Alvaro de Souza [UNESP]; Hott, M. B. [UNESP] (Amer Physical Soc, 2012)
In this work we apply point canonical transformations to solve some classes of nonautonomous, nonlinear Schrodinger equations, namely, those which possess specific cubic and quintic (time- and space-dependent) nonlinearities. In this way we generalize some procedures recently published which resort to an ansatz to the wave function and recover a time- and space-independent nonlinear equation which can be solved explicitly. The method applied here allows us to find wide localized (in space) soliton solutions to the nonautonomous, nonlinear Schrodinger equation. We also generalize the external potential which traps the system and the terms of the nonlinearities.